Cognitive disparity in online rumor perception: a group analysis during COVID-19 - Chao Shen; Pengyu He; Zhenyu Song; Yimeng Zhang (BMC Public Health)
Abstract Background The harmonious cognitive alignment among various netizen groups is pivotal for the spread and amplification of online rumors. This alignment, characterized by shared cognitive inclinations, fosters uniformity in attitudes and perspectives, thereby precipitating synchronized engagement in the dissemination of such rumors. Notably, discernible disparities emerge in group cognition as different types of rumors pertaining to the same event propagate. This research endeavors to dissect the roles of netizen groups through the lens of cognitive variance, thereby attaining a more profound comprehension of the distinctive traits and behavioral dynamics of various netizen factions in the context of online rumor dissemination. Methods By integrating Bloom’s taxonomy and crafting a survey questionnaire, this study captured the cognitive responses of netizens to various online rumor themes across two critical dimensions: (1) Information Cognition: exploring cognitive processing levels from basic recall to application and analysis and (2) Attitude Change: evaluating higher-order cognitive processes such as evaluating and creating in response to complex rumor scenarios. The decision tree classification algorithm was meticulously applied to dissect the catalysts behind the cognitive shifts among netizens. Additionally, the K-Means clustering algorithm was effectively utilized to categorize netizen groups along thematic lines, offering a nuanced view of their cognitive engagement. Results The initial impression of a rumor significantly influences netizens’ final cognitive perceptions. Twelve characteristics were observed in netizen groups during the dissemination of rumors on different themes, and these groups were classified into four categories: knowledge-oriented, competition-oriented, social-oriented, and entertainment-oriented, based on their cognitive differences. Conclusions Throughout the lifecycle of online rumors, from inception to dissemination, diverse netizen groups assume distinct roles, each exerting a unique influence on the spread and reception of information. By implementing tailored governance strategies that are sensitive to the characteristics of these groups, it is possible to attain substantially more effective outcomes in managing the propagation of online rumors. This nuanced approach to governance recognizes the heterogeneity of the online community and leverages it to enhance the efficacy of interventions.